Pengaruh Slow Stroke Back Massage Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Rsud Rejang Lebong Tahun 2025 - Ninda Putri Arishandi; Des Metasari; Delta Aprianti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypertension is a non-communicable disease with a high incidence and a risk of serious complications such as stroke and heart failure. Hypertension management involves more than just pharmacological therapy; it can also be supported by non-pharmacological therapies. One simple, safe, and effective non-pharmacological intervention is Slow Stroke Back Massage (SSBM), which provides a relaxing effect and helps lower blood pressure. Objective: To determine the effect of Slow Stroke Back Massage on lowering blood pressure in hypertensive patients in Melati Ward of RSUD Rejang Lebong Regency. This study was a quasi-experimental study with a pre-test, post-test, and control group design. The sample size was 48 respondents, divided into 24 in the intervention group and 24 in the control group using a purposive sampling technique. Data analysis began with a normality test using the Shapiro-Wilk test and a homogeneity test using Levene's test. Furthermore, a paired t-test was used to determine differences in blood pressure before and after treatment in each group. In the intervention group, the average systolic blood pressure decreased from 152.5 mmHg to 122.08 mmHg, a difference of 30.41 mmHg (p = 0.000), while the average diastolic blood pressure decreased from 94.2 mmHg to 79.6 mmHg, a difference of 14.58 mmHg (p = 0.000). In the control group, the average systolic blood pressure decreased from 160.4 mmHg to 147.5 mmHg, a difference of 12.91 mmHg (p = 0.003), while the average diastolic blood pressure decreased from 99.6 mmHg to 91.3 mmHg, a difference of 8.33 mmHg (p = 0.005). Slow Stroke Back Massage has been shown to be effective in reducing both systolic and diastolic blood pressure in hypertensive patients. This intervention can be used as a simple, safe, and affordable non-pharmacological therapy, and can be implemented by healthcare professionals and patients' families as an adjunct to pharmacological therapy.